Karakteristik Kimia dan Organoleptik Nugget Ikan Layur (Trichiurus lepturus) dan Layang Benggol (Decapterus russelli) dengan Fortifikasi Tepung Daun Kelor (Moringa oleifera) - Rahmawanti, Mutia D; Mustofa, Akhmad; Karyantina, Merkuria (Universitas Pattimura, 2024)
Nuggets are a frozen food product that can be consumed after frying. Nuggets made from largehead hairtail and Indian scad were chosen to enhance the functional value of the fish, which is rich in fatty acids, particularly unsaturated fatty acids. Moringa leaves flour, known for its high fiber content, was added to improve the nutritional value of the nuggets further. This study aimed to determine the characteristics of largehead hairtail and Indian scad fish nuggets fortified with moringa leaf flour, focusing on their protein and fiber content. The experiment was conducted using a Completely Randomized Design with two factors: (1) the ratio of largehead hairtail to Indian scad and (2) the substitution of moringa leaf flour for wheat flour. The nugget formulation with the highest protein and fiber content was achieved using 10% moringa leaf flour and 90% wheat flour, combined with a 50:50 ratio of largehead hairtail to Indian scad. This formulation resulted in a moisture content of 40,74%, ash content of 2,15%, fat content of 11,93%, protein content of 11,53%, crude fiber of 9,94%, and sensory score of 3.30 (somewhat like). Nuggets made from largehead hairtail and Indian scad, fortified with moringa leaf flour, can serve as a ready-to-eat food product with a high protein and fiber content.